Disproportionate COVID-19 vaccine acceptance rate among healthcare professionals on the eve of nationwide vaccine distribution in Bangladesh. (2nd September 2021) - Alam, A.B.M. Muksudul; Azim Majumder, Md Anwarul; Haque, Mainul; Ashraf, Fatema; Khondoker, Mohib Ullah; Mashreky, Saidur Rahman; Wahab, Abrar; Siddiqui, Tosaddeque Hossain; Uddin, Aftab; Joarder, Taufique; Ahmed, S.M. Moslehuddin; Deeba, Farzana; et al.
ABSTRACT: Background: Acceptance of the COVID-19 vaccine by the target groups would play a crucial role in stemming the pandemic. Healthcare professionals (HCPs) are the priority group for vaccination due to them having the highest risk of exposure to infection. This survey aimed to assess their acceptance of COVID-19 vaccines in Bangladesh. Research design and methods: A cross-sectional survey using an online questionnaire was conducted between January 3 to 25, 2021, among HCPs (n = 834) in Bangladesh. Results: Less than 50% of HCPs would receive the vaccine against COVID-19 if available and 54% were willing to take the vaccine at some stage in the future. Female participants (OR:1.64;95%CI:1.172–2.297), respondents between 18–34 years old (OR:2.42; 95% CI:1.314–4.463), HCPs in the public sector (OR:2.09; 95% CI:1.521–2.878), and those who did not receive a flu vaccine in the previous year (OR:3.1; 95% CI:1.552–6.001) were more likely to delay vaccination. Conclusions: The study revealed that, if available, less than half of the HCPs would accept a COVID-19 vaccine in Bangladesh. To ensure the broader success of the vaccination drive, tailored strategies and vaccine promotion campaigns targeting HCPs and the general population are needed.